Aninhamento de assembleias de aves em arquipélagos oceânicos - Caetano, Vinne Magalhães (2021)
The species richness of an island can be driven by the quality, complexity and heterogeneity of the habitat, as well as the dispersal ability of the species. Island size and altitude can be used as surrogate variables for habitat attributes, and island isolation can be used to represent the dispersal ability of species. Communities on a gradient of isolation or environmental complexity can form a taxonomically and/or morphologically nested distribution pattern. I tested the morphological nesting of bird assemblages from islands of eight oceanic archipelagos for size, altitude, and isolation of their islands. I performed this test by weighting the nesting by the magnitude of the difference between the tested variable and without this weighting. I found that morphological nesting was predominantly relevant to size and altitude, while isolation was not able to explain nesting in any archipelago. Unweighted analyzes had more positive results for nesting than those weighted by difference in altitude, size or isolation. The nesting observed was more due to richness shared between communities than due to the tree topology of morphological similarity between species. This means that if a community shares similarity in attributes with other communities, this similarity in attributes comes from the species shared between these communities and not from different species with similar attributes. Isolation was not able to explain the nesting, however, it is possible that there are isolation measures with greater biological relevance.